Pivotal Role of Iron Homeostasis in the Induction of Mitochondrial Apoptosis by 6-Gingerol Through PTEN Regulated PD-L1 Expression in Embryonic Cancer Cells - Sp, Nipin; Kang, Dong Young; Jo, Eun Seong; Lee, Jin-Moo; Bae, Se Won; Jang, Kyoung-Jin (Frontiers in Oncology, 2021)
Embryonic cancer stem cells (CSCs) can differentiate into any cancer type. Targeting CSCs with natural compounds is a promising approach as it suppresses cancer recurrence with fewer adverse effects. 6-Gingerol is an active component of ginger, which exhibits well-known anti-cancer activities. This study determined the mechanistic aspects of cell death induction by 6-gingerol. To analyze cellular processes, we used Western blot and real-time qPCR for molecular signaling studies and conducted flow cytometry. Our results suggested inhibition of CSC marker expression and Wnt/β-catenin signaling by 6-gingerol in NCCIT and NTERA-2 cells. 6-Gingerol induced reactive oxygen species generation, the DNA damage response, cell cycle arrest, and the intrinsic pathway of apoptosis in embryonic CSCs. Furthermore, 6-gingerol inhibited iron metabolism and induced PTEN, which both played vital roles in the induction of cell death. The activation of PTEN resulted in the inhibition of PD-L1 expression through PI3K/AKT/p53 signaling. The induction of PTEN also mediated the downregulation of microRNAs miR-20b, miR-21, and miR-130b to result in PD-L1 suppression by 6-gingerol. Hence, 6-gingerol may be a promising candidate to target CSCs by regulating PTEN-mediated PD-L1 expression.